2008
DOI: 10.1097/hjh.0b013e32830e4932
|View full text |Cite
|
Sign up to set email alerts
|

Reference values of aortic pulse wave velocity in the elderly

Abstract: In elderly individuals of 60-75 years, an AoPWV value below 10 m/s, measured with the PulsePen device, can be considered as a normal value. Values of 10-13 m/s can be considered as 'high normal' or 'borderline', whereas an AoPWV above 13 m/s is frankly elevated. This study provides, for the first time in the elderly, reference values of AoPWV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 23 publications
1
39
0
2
Order By: Relevance
“…12,27 Both use electrocardiogram-gated sequential tonometric measurements to asses aortic (carotid-femoral) PWV and are widely used in clinical and research practice. [23][24][25] Survival studies in adults indicate that PWV measured by applanation tonometry has a good clinical predictive value. 20 Involving more than 1000 children, our research group has furthermore confirmed the applicability of the PP device to mass screening of children of different age groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,27 Both use electrocardiogram-gated sequential tonometric measurements to asses aortic (carotid-femoral) PWV and are widely used in clinical and research practice. [23][24][25] Survival studies in adults indicate that PWV measured by applanation tonometry has a good clinical predictive value. 20 Involving more than 1000 children, our research group has furthermore confirmed the applicability of the PP device to mass screening of children of different age groups.…”
Section: Discussionmentioning
confidence: 99%
“…They are easily applied in adults and children and have a fair reproducibility. [22][23][24][25][26] PP and SC devices have been validated invasively in adults. 12,27 It is claimed that, in children, PWV measurements by applanation tonometry may be difficult to carry out as they are time consuming and require some degree of patient cooperation.…”
Section: Introductionmentioning
confidence: 99%
“…Our results establish reference values for less healthy adult men and women separately, whereas in healthy people, we defined the same values for men and women. The effect of gender on reference values has been analyzed for Caucasian (Alecu et al 2008;Boutouyrie and BMI body mass index, WC waist circumference, HC hip circumference, WHR waist-to-hip ratio, SBP systolic blood pressure, DBP diastolic blood pressure, PP pulse pressure, MBP mean blood pressure, PWV pulse wave velocity, HDL-C high-density lipoprotein cholesterol, LDL-C low-density lipoprotein cholesterol, TC total cholesterol, TGL triglycerides Vermeersch 2010; Reusz et al 2010) but not for African (Shiburi et al 2006) populations. In two of these studies, values were defined separated by gender, (Alecu et al 2008;Reusz et al 2010) but not in the other one because they found a small effect of gender on PWV values (Boutouyrie and Vermeersch 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of gender on reference values has been analyzed for Caucasian (Alecu et al 2008;Boutouyrie and BMI body mass index, WC waist circumference, HC hip circumference, WHR waist-to-hip ratio, SBP systolic blood pressure, DBP diastolic blood pressure, PP pulse pressure, MBP mean blood pressure, PWV pulse wave velocity, HDL-C high-density lipoprotein cholesterol, LDL-C low-density lipoprotein cholesterol, TC total cholesterol, TGL triglycerides Vermeersch 2010; Reusz et al 2010) but not for African (Shiburi et al 2006) populations. In two of these studies, values were defined separated by gender, (Alecu et al 2008;Reusz et al 2010) but not in the other one because they found a small effect of gender on PWV values (Boutouyrie and Vermeersch 2010). However, this adjustment is needed for practical use considering the gender-related pattern of CV morbidity and mortality (Lerner and Kannel 1986;Anderson et al 1991;Li et al 2006;Shaw et al 2008;Maas and Appelman 2010;Claassen et al 2012;Yang and Kozloski 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation